2017
DOI: 10.1186/s12944-017-0443-4
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of effects of DPP-4 inhibitor and SGLT2 inhibitor on lipid profile in patients with type 2 diabetes

Abstract: BackgroundPrevious studies suggest that dipeptidyl peptidase-4 (DPP-4) inhibitors and sodium glucose cotransporter 2 (SGLT2) inhibitors have different effects on the lipid profile in patients with type 2 diabetes. We investigated the effects of DPP-4 inhibitors and SGLT2 inhibitors on the lipid profile in patients with type 2 diabetes.MethodsFrom January 2013 to December 2015, a total of 228 patients with type 2 diabetes who were receiving a DPP-4 inhibitor or SGLT2 inhibitor as add-on therapy to metformin and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
47
3
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(58 citation statements)
references
References 35 publications
7
47
3
1
Order By: Relevance
“…Previously, we showed through cross‐sectional analysis, which we confirmed in this paper, that moving levels of local service performance and prescribing of metformin and sulphonylureas from the median to the 90th percentile level might be associated with 2 10 000 additional patients achieving TGC and 62 000 fewer at HGR. The associations between change in SGLT2 inhibitor and DPP‐4 inhibitor prescription at a practice level and the proportions of patients achieving TGC and at HGR may be important, if the link is causative . Improving glucose control by using new drugs would be costly, although the present findings suggest, for example, that an investment of £50 m in additional SGLT2 inhibitors in those practices prescribing around or below the national average level would include an additional 1 00 000 patients and could bring as many as 12 500 patients out of HGR and 20 000 into TGC.…”
Section: Discussionmentioning
confidence: 76%
“…Previously, we showed through cross‐sectional analysis, which we confirmed in this paper, that moving levels of local service performance and prescribing of metformin and sulphonylureas from the median to the 90th percentile level might be associated with 2 10 000 additional patients achieving TGC and 62 000 fewer at HGR. The associations between change in SGLT2 inhibitor and DPP‐4 inhibitor prescription at a practice level and the proportions of patients achieving TGC and at HGR may be important, if the link is causative . Improving glucose control by using new drugs would be costly, although the present findings suggest, for example, that an investment of £50 m in additional SGLT2 inhibitors in those practices prescribing around or below the national average level would include an additional 1 00 000 patients and could bring as many as 12 500 patients out of HGR and 20 000 into TGC.…”
Section: Discussionmentioning
confidence: 76%
“…Two other placebo-controlled studies of dapagliflozin (10 mg) for a duration of 12 [45] and 24 weeks [46] revealed the ability of this drug to significantly reduce small dense LDL-C (p < 0.005 vs. sitagliptin and p < 0.003 for intergroup comparison) but not the less atherogenic large LDL-C (p < 0.026 vs. sitagliptin, p < 0.671 for intergroup comparison). Interestingly, HDL-2-C (a well-known marker inversely associated with triglyceride levels and insulin resistance) was found to be significantly increased (p < 0.001 vs sitagliptin; p < 0.013 for intergroup comparison) [45].…”
Section: Sodium Glucose Cotransporter-2 Inhibitors (Sglt2-is)mentioning
confidence: 98%
“…Interestingly, further studies comparing linagliptin and gemigliptin vs. dapagliflozin (oriented to add-on therapy to metformin and/or sulfonylurea for 24-weeks) demonstrated a significant increase in HDL-C levels in subjects treated with SGLT-2is [46].…”
Section: Sodium Glucose Cotransporter-2 Inhibitors (Sglt2-is)mentioning
confidence: 99%
“…One explanation could be that these drugs cause a switch from carbohydrate to lipid utilization, thereby increasing hepatic fatty acids levels to induce ketone and hepatic TC production. Empagliflozin was also associated to a lower LDL receptor expression and LDLc catabolism (198). Drug-induced effects on serum lipid levels and CV risk are summarized in Table 8.…”
Section: Sglt-2 Inhibitorsmentioning
confidence: 99%